PENGARUH FIRM SIZE, LEVERAGE DAN PENGHINDARAN PAJAK TERHADAP MANAJEMEN LABA (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2014-2016) - Hasmi Ridaningwahyu, 14.05.52.0076; Wahyudi, Djoko (Students Journal of Accounting and Banking, 2018)
The practice of earnings management is a common behavior undertaken by management. Earnings management is the actions of managers in the process of preparing financial statements in order to gain personal gain.This study aims to examine and analyze the effect of firm size, leverage and tax avoidance on earnings management.The sample in this study used 207 data from 69 manufacturing companies listed in Indonesia Stock Exchange for period 2014-2016 using purposive sampling method. The analysis tools used are normality test, classical assumption test, multiple linear regression test, and model test.Based on the research that has been done, found the result that firm size has a significant negative effect to earnings management, leverage has positive effect not significant to earnings management, tax avoidance has negative effect not significant to earnings management.Keywords:Firm Size, Leverage, Tax Avoidance and Earnings Management